2004
DOI: 10.1088/0029-5515/44/12/s11
|View full text |Cite
|
Sign up to set email alerts
|

High pressures generated by laser driven shocks: applications to planetary physics

Abstract: High power lasers are a tool that can be used to determine important parameters in the context of Warm Dense Matter, i.e. at the convergence of low-temperature plasma physics and finite-temperature condensed matter physics. Recent results concerning planet inner core materials such as water and iron are presented. We determined the equation of state, temperature and index of refraction of water for pressures up to 7 Mbar. The release state of iron in a LiF window allowed us to investigate the melting temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…shock experiments). This difference is commonly explained by a "superheating" effect during shocks at large pressures (Koenig et al, 2004). Data are highly uncertain above 200 GPa.…”
Section: Modeling the Deep Interiormentioning
confidence: 99%
“…shock experiments). This difference is commonly explained by a "superheating" effect during shocks at large pressures (Koenig et al, 2004). Data are highly uncertain above 200 GPa.…”
Section: Modeling the Deep Interiormentioning
confidence: 99%
“…We are performing Monte-Carlo proton scattering modeling to reconstruct the density profile of the release. 6 Although in this project we successfully created isochorically heated plasmas in the 10-20eV range we found that the spatial resolution of the proton probe beam able to be created on the JanUSP laser would be insufficient to probe a density front in solid material to the degree required for an accurate EOS measurement. Recent experiments performed with collaborators at LLNL 7 on high energy K-alpha x-ray production have suggested that it may be possible to generate an x-ray source with sufficiently high energy, and sufficiently small source size, to radiograph the density front in an isochorically heated material.…”
Section: Results/technical Outcomementioning
confidence: 96%
“…Recent results from experi- ments conducted on the Omega laser have measured Hugoniot data for high pressure, dense helium, 79 the shock induced transformation of liquid hydrogen into a metallic fluid, 80 and electronic conduction in shock-compressed water. 81 Additionally, high pressure, shock compressed iron has been measured on the LULI and Vulcan lasers, 82 and the shock compressed EOS of liquid hydrogen has been measured on the Z magnetic pinch facility. 83 With NIF, experiments could be done, for the first time, to measure the EOS of planetary constituents at pressures approaching those at the centers of the giant planets.…”
Section: F Planetary Interiorsmentioning
confidence: 99%